Exploring resilience and self-efficacy as predictors of sustainable behaviour through structural equation modelling - Nor Azma Rahlina; Xu, YanHong; Ahmad Shakani Abdullah (Universiti Malaysia Sabah, 2024)
Sustainability behavior in universities is increasingly recognized as a vital component of fostering environmental consciousness among university members, particularly academic staff. These elements not only enhance university member’s commitment to sustainable practices but also foster a supportive environment for green initiatives. While individual psychological factors like resilience and self-efficacy are crucial, many studies neglect how these traits interact with external factors. Thus, the objective of this study is to examine the influence of transformational leadership on sustainable behaviour practice, with a focus on how resilience and self-efficacy as mediators in this relationship. The respondents are academic staffs from Guangdong Province, representing key participants in implementing and experiencing campus sustainability practices. Using a sample of 241 academic staff from universities in Guangdong, the sample size was carefully determined with G*Power for adequate statistical power and selected through a convenience sampling method. The data was analysed using Structural Equation Modelling (SEM) with SmartPLS 4, a powerful tool for evaluating complex relationships between variables. The results show that while transformational leadership plays a key role in fostering positive attitudes toward sustainability behaviour, it doesn’t directly translate into more active engagement in sustainable practices. In additional, the study reveals that resilience and self-efficacy act as important mediators in the relationship between transformational leadership and sustainability behaviour. Transformational leadership helps build these qualities, and in turn, it drives individuals to engage more deeply in sustainable actions. This suggests that leadership can inspire positive thinking, but it’s the inner strength and confidence of individuals that truly make a difference in turning those attitudes into real, sustainable behaviour. This research provides critical insights for academic leaders and policymakers aiming to promote and enhance sustainable behaviour practices within academic institutions, offering a deeper understanding of the psychological mechanisms and leadership that drive sustainability behaviour.